Hormonal aspects of skin hyperpigmentation in healthy Kurdish primigravida women in Erbil City - Renas Najat Saleem; Sarbaz Ibrahim Mohammed (Zanco Journal of Pure and Applied Sciences, 2021)
The present study aimed to determine some hormonal and biochemical aspects of skin pigmentation in pregnant women. The longitudinal study included forty-three healthy volunteers; ages ranged between 16-28 years, monitored from the beginning of gestation to delivery of birth. Then, women were divided into two groups (25 pigmented and 18 non-pigmented women) to evaluate hormonal and biochemical criteria. The result revealed a significant elevation in adrenocorticotropic hormones (ACTH), estrogen, progesterone hormone levels in pigmented women, and the progressing gestational period significantly changed the hormonal level, liver function parameters. At the same time, Alanine transaminase (ALT) reduced considerably in the first trimester. We concluded that skin pigmentation in primigravida women is associated with elevated ACTH, female sex hormones level, and liver enzymes. Hyperpigmentation was slightly evident in pregnant mothers with female fetuses than male fetuses.